2020
DOI: 10.1101/2020.04.08.022269
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cognitive Flexibility Deficits in Rats with Dorsomedial Striatal 6-OHDA Lesions Tested Using a 3-Choice Serial Reaction Time Task with Reversal Learning

Abstract: Lesions of the dorsomedial striatum elicit deficits in cognitive flexibility that are an early feature of Parkinson's disease (PD), and presumably reflect alterations in frontostriatal processing. The current study aimed to examine deficits in cognitive flexibility in rats with bilateral 6hydroxydopamine (6-OHDA) lesions in the dorsomedial striatum. While deficits in cognitive flexibility have previously been examined in rodent PD models using the cross-maze, T-maze, and a food-digging task, the current study … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…The copyright holder for this preprint (which this version posted April 9, 2020. ; https://doi.org/10.1101/2020.04.08.022269 doi: bioRxiv preprint test cognitive flexibility in rats with 6-hydroxydopamine (6-OHDA) lesion to the bilateral dorsomedial striatum. Whereas past research has generally used lever press in the 5-CSRT, it has been shown that nose poke is an easier response to learn in rats [9]. We therefore chose nose poke, which has been used in more recent 5-CSRT studies [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…The copyright holder for this preprint (which this version posted April 9, 2020. ; https://doi.org/10.1101/2020.04.08.022269 doi: bioRxiv preprint test cognitive flexibility in rats with 6-hydroxydopamine (6-OHDA) lesion to the bilateral dorsomedial striatum. Whereas past research has generally used lever press in the 5-CSRT, it has been shown that nose poke is an easier response to learn in rats [9]. We therefore chose nose poke, which has been used in more recent 5-CSRT studies [6,7].…”
Section: Introductionmentioning
confidence: 99%